A Mediation Analysis of Self-Esteem in the Relationship between Dark Triad and Loneliness among Future Science Educators - Rizki Nor Amelia; Prasetyo Listiaji; Parmin Parmin; Amnan Haris; Tiara Dwi Wulandari; Luky Hidayat; Ahmad Dif Fairuz Zaidan (Universitas Nahdatul Ulama Surabaya, 2026)
This study examined the structural relationships among Dark Triad traits, self-esteem, and loneliness, with particular emphasis on the mediating role of self-esteem. A quantitative cross-sectional survey design was employed, involving 165 prospective science teachers (M_age = 18.53, SD = 1.10) enrolled in the Science Education Study Program at Universitas Negeri Semarang. Participants meeting predefined inclusion criteria voluntarily completed three validated self-report measures: the Short Dark Triad (SD3), the UCLA Loneliness Scale, and the Rosenberg Self-Esteem Scale. Data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) and hierarchical regression analysis. The results indicated that Dark Triad traits negatively predicted self-esteem (β = −0.93, p < .001) and positively predicted loneliness (β = 0.97, p < .001), whereas self-esteem negatively predicted loneliness (β = −0.96, p < .001). When self-esteem was included in the model, the direct effect of Dark Triad traits on loneliness decreased (β = 0.63), and the Sobel test confirmed a significant partial mediation effect (Z = 6.13, SE = 0.04, p < .001). These findings suggest that self-esteem functions as a protective psychological mechanism that attenuates the adverse effects of Dark Triad traits on loneliness. Accordingly, interventions aimed at strengthening self-esteem may contribute to enhancing the social and emotional well-being of prospective science educators.